2011
DOI: 10.1007/s11575-011-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Does National Context Affect Target Firm Employees’ Trust in Acquisitions?

Abstract: Abstract In this study, we test the assumption that the way target firm employees respond to a takeover is contingent on their national origin.  The antecedents of target firm member trust in the acquiring firm management were examined in a cross-national sample of German and Singaporean employees using a policy-capturing design.  Five factors hypothesized to affect target firm member trust after a takeover were found to be significant influences on employees' trust judgments in a decisionmaking simulation:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 110 publications
(139 reference statements)
0
36
0
Order By: Relevance
“…More importantly, these authors also note that ''future research on POS should continue to explore whether the relationships hold across cultures, whether they differ in strength, whether new antecedents or outcomes are relevant, and why' ' (p. 139). This study responds to such calls for research by offering theoretical clarifications supported by meta-analytic evidence (Bausch and Krist 2007;Reus and Rottig 2009;Stahl and Chua 2012;Tan and Sousa 2013).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…More importantly, these authors also note that ''future research on POS should continue to explore whether the relationships hold across cultures, whether they differ in strength, whether new antecedents or outcomes are relevant, and why' ' (p. 139). This study responds to such calls for research by offering theoretical clarifications supported by meta-analytic evidence (Bausch and Krist 2007;Reus and Rottig 2009;Stahl and Chua 2012;Tan and Sousa 2013).…”
Section: Introductionmentioning
confidence: 79%
“…Meta-analytic tests are necessary to start addressing mixed findings originating from primary studies across the world (Bausch and Krist 2007;Reus and Rottig 2009;Stahl and Chua 2012;Tan and Sousa 2013). If guidance is sought in the existing literature, the likely role of the cultural context in the POS-OCB relationship is either unclear or puzzling.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the informal institutional distance, the more challenging it would be for the MNE make sense of the local organizational culture, understand and connect with the local employees and ultimately establish a solid base for knowledge exchange. Furthermore, past research has found that the lack of trust in the local management is often a deal-breaker in CB M&As (Very and Schweiger 2001;Stahl et al 2012). Informal institutional differences, often associated with cultural differences, can lead to the use of ambiguous language in the acquisition agreement which in turn can exacerbate the lack of trust between the negotiating parties in a CB M&A, create conflicts and disputes as MNEs seek to finalize the M&A deal (Dikova et al 2010) and finally cause delays in the post-acquisition integration process (Bruner 2005).…”
Section: Informal Institutional Distance and Ownership Strategies In mentioning
confidence: 99%
“…Harris & Ravenscraft 1991;Mann and Kohli 2011), postacquisition integration dynamics (e.g. Vaara 2003;Stahl et al 2012), and post-acquisition performance (e.g. Dikova and Sahib 2013;Chang and Tsai 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The EMNEs will suffer from both liability of foreignness as well as liability of country of origin (Cartwright & Price, 2003;Elango & Sethi, 2007;Harvey, et al, 2005;Lee & Lee, 2011;Luo, et al, 2002;Moeller, et al, 2013;Stevens & Shenkar, 2012;Zaheer, 1995). The national context of the acquirer can greatly affect the level of trust that target's employees place on the acquirer companies (Rottig, 2013;Stahl, Chua, & Pablo, 2012).…”
Section: Leadership Trustmentioning
confidence: 99%